The beginning of library education in the universities of the Soviet Union - Гудаускас, Реналдас (Knygotyra, 1991)
The author analyses the founding of the departments of library and bibliography sciences in the universities of the republics of the Soviet Union. He shows the historical sources of this tradition, analyses the first attempts made in the USSR. More attention is paid to the existing departments of library and bibliography sciences in Vilnius, Ryga, Baku, Kishiniov and other universities. The main stress is laid on organizational aspect of the process of founding such departments and the conditions of their work in the environment of other specialities, their influence on training of librarians.